Effectiveness of Experiential Learning–Based Clinical Education on Nurses' Clinical Decision-Making: A Systematic Review - Ayu Trisnadewi; Elsye Maria Rosa (Indonesian Journal of Global Health Research, 2026)
Clinical decision-making is a core competency for nurses that directly impacts patient safety. However, the development of this skill is often not automatic and faces barriers such as service complexity and lack of confidence. Experiential learning through a cycle of concrete experiences and reflection offers an approach to bridge this competency gap. This study aims to synthesize scientific evidence regarding the types of experiential learning interventions in clinical education and assess their impact on nurses' clinical decision-making or judgment. The study design was a systematic review following the PRISMA 2020 guidelines. A literature search was conducted in PubMed/MEDLINE, Scopus, and CINAHL databases for articles published between 2011 and 2025. Inclusion criteria included RCTs or quasi-experimental studies involving nurses or nursing students in clinical settings with experience-based interventions. Nine studies met the inclusion criteria and were analyzed narratively. Data synthesis identified two main themes. First, intervention modalities included realistic clinical simulations, in-situ simulations in the ICU, scenario-based triage training, interactive cognitive techniques (such as critical thinking cards), and structured reflection methods such as Debriefing for Meaningful Learning (DML). Second, these interventions consistently improved clinical decision accuracy, reasoning, knowledge, and service time efficiency. The use of DML was shown to be more effective in improving clinical reasoning than traditional debriefing. However, some studies have shown a decline in retention of the effect after three months, emphasizing the need for ongoing training. Experiential learning-based clinical education is effective in improving the quality of nurses' clinical decisions. The success of this intervention depends heavily on the integration of structured exposure to clinical experiences with systematic reflection mechanisms. Hospital management is advised to implement regular scenario-based training and strengthen the capacity of facilitators in conducting debriefings to ensure patient safety and the quality of nursing care.